2003
DOI: 10.1111/1467-9280.t01-1-01427
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Effort in Perceiving Distance

Abstract: Berkeley proposed that space is perceived in terms of effort. Consistent with his proposal, the present studies show that perceived egocentric distance increases when people are encumbered by wearing a heavy backpack or have completed a visual-motor adaptation that reduces the anticipated optic flow coinciding with walking effort. In accord with Berkeley's proposal and Gibson's theory of affordances, these studies show that the perception of spatial layout is influenced by locomotor effort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
459
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 476 publications
(501 citation statements)
references
References 11 publications
32
459
1
5
Order By: Relevance
“…That movement quickly ran its course without having much impact, but, today, research again suggests that perception of the physical world is influenced by emotion and other internal factors. For example, Proffitt and colleagues (e.g., Bhalla & Proffitt, 1999;Proffitt, Stefanucci, Banton & Epstein, 2003;Witt, Proffitt, & Epstein, 2004) have found that hills appear steeper and distances farther to people with reduced physical resources, either from wearing a heavy backpack, being physically tired, or being elderly. Recent research shows that emotion can have similar effects.…”
Section: B the Affective Regulation Of Perceptionmentioning
confidence: 99%
“…That movement quickly ran its course without having much impact, but, today, research again suggests that perception of the physical world is influenced by emotion and other internal factors. For example, Proffitt and colleagues (e.g., Bhalla & Proffitt, 1999;Proffitt, Stefanucci, Banton & Epstein, 2003;Witt, Proffitt, & Epstein, 2004) have found that hills appear steeper and distances farther to people with reduced physical resources, either from wearing a heavy backpack, being physically tired, or being elderly. Recent research shows that emotion can have similar effects.…”
Section: B the Affective Regulation Of Perceptionmentioning
confidence: 99%
“…Second, participants are instructed to remain completely still with their heads immobilized with padding. This is potentially problematic given that the ability to act is known to alter spatial perception (e.g., Proffitt, Stefanucci, Banton, & Epstein, 2003;Witt, Proffitt, & Epstein, 2004;Lourenco & Longo, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…As a result, hills look steeper to people experiencing fear of descending them (Stefanucci, Proffitt, Clore, & Parekh, 2008) and geographical space looks longer to those wearing a heavy backpack (Proffitt, Stefanucci, Banton, & Epstein, 2003) or standing on a hill (Stefanucci, Proffitt, Banton, & Epstein, 2005). Additionally, metaphor provides a straightforward link between the physical and the representational, enabling people to comprehend abstract concepts by grounding them in concrete sensorimotor experience (Clark, 1973;Lakoff & Johnson, 1980).…”
mentioning
confidence: 99%